O13 Acid ceramidase: a potential biomarker for locally advanced rectal cancer?. (30th July 2021) - Clifford, Rachael Elizabeth; Govindarajah, Naren; Bowden, David; Sutton, Paul; Parsons, Jason; Vimalachandran, Dale
Abstract: Introduction: We have previously utilized proteomic and immuno-histochemical data to validate that high levels of acid ceramidase (AC) expression confers poorer neoadjuvant response in rectal cancer. Biological (siRNA, plasmid and CRISPR) AC manipulation altered radiosensitivity in-vitro. We aimed to assess the radiosensitising effect of pharmacological AC inhibitions and elucidate the potential underlying mechanism. Methods: Optimal drug dosing was achieved using ELISA activity assays in multiple colorectal cancer cell lines (HCT116, HT29, LIM1215). Carmofur and a novel small molecular inhibitor (LCL521) were used as pharmacological inhibitors. Standard clonogenic assays assessed cell survival following increasing irradiation (2 D), volume change in 3 D spheroids and cell viability in patient derived organoids. Annexin V/PI staining was used to determine apoptosis. Results: Carmofur clonogenic assays demonstrated reduced colony formation efficiency (CFE) and improved radiosensitivity across cell lines. HCT116 showed 0.438(CFE) control v 0.183(CFE) carmofur at 1 Gy, 0.140(CFE) control v 0.076(CFE) at 2 Gy ( P  = 0.000563). LCL521 dosing improved radiosensitivity in spheroid models. HCT116 volume day-15 2.36x10-5mm v control 4.15x10-5mm. siRNA-AC demonstrated increased apoptosis across time points compared to NT control ( P  = 0.035), and increased poly-ADP ribose polymerase-1 (PARP-1) cleavage in a p53-dependent process. Conclusion: Initial work demonstrates that pharmacological inhibition of AC produces comparative radiosensitizing effects in these cell lines and cancer models. siRNA-AC increases apoptosis, suggestive of a potential underlying mechanism. This work further solidifies AC as a potential biomarker, however further recapitulation in more complex models and ultimately in-vivo is required to establish a translatable clinical role.